2017
DOI: 10.1016/j.jsat.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of the use of screening, brief intervention, and referral to treatment (SBIRT) for drug and alcohol use with jail inmates

Abstract: Background Screening, brief intervention, and referral to treatment (SBIRT) is an evidence-based practice that has been shown to reduce alcohol and drug use in healthcare, educational, and other settings, but research on the effectiveness of SBIRT with populations involved in the criminal justice system is limited. These populations have high rates of substance use but have limited access to interventions. Methods The study randomized 732 jail inmates from a large urban jail to the SBIRT intervention or to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…These findings are hypothesis-generating in suggesting that motivational interventions may not be helpful for increasing problem recognition among justice-involved individuals with a SUD, as they are designed to do, or may be unhelpful in this domain. Other studies with jail populations found null results of motivational interventions on other outcomes such as treatment engagement [ 30 ]. Of note, our results should be interpreted with caution, given the small sample, post hoc nature of these analyses, multiple comparisons, and that the parent study did not include a no-treatment control condition.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are hypothesis-generating in suggesting that motivational interventions may not be helpful for increasing problem recognition among justice-involved individuals with a SUD, as they are designed to do, or may be unhelpful in this domain. Other studies with jail populations found null results of motivational interventions on other outcomes such as treatment engagement [ 30 ]. Of note, our results should be interpreted with caution, given the small sample, post hoc nature of these analyses, multiple comparisons, and that the parent study did not include a no-treatment control condition.…”
Section: Discussionmentioning
confidence: 99%
“…A guideline for reporting the results of qualitative studies specifies that researchers' characteristics (including personal attribution, relationship with participants) should be reported because they influence the results [20]. Regarding personal outcomes (q3.3), some articles only reported that researchers held informal small group discussions [21,22]. If provided with this information, readers would gain a better understanding of the project including the CBPR process.…”
Section: Discussionmentioning
confidence: 99%
“…Brief interventions often apply the screening, brief intervention, and referral to treatment (SBIRT) model that is commonly used to successfully assess and treat alcohol problems (33,34). SBIRT’s brief yet effective format makes it desirable for forensic populations, and although this treatment model has been utilized in a limited capacity within forensic populations, preliminary investigations into its feasibility and efficacy in addressing addictive behaviors are promising (35). Further research is needed to evaluate SBIRT for use with forensic populations, as well as to adapt the SBIRT model to the characteristics and needs of this specific population.…”
Section: Gambling Attitudesmentioning
confidence: 99%